Language and Automata Theory and Applications Third International Conference, LATA 2009, Tarragona, Spain, April 2-8, 2009. Proceedings - Dediu, Adrian Horia; Ionescu, Armand Mihai; Martin-Vide, Carlos (Theoretical Computer Science and General Issues,, 2009)
This book constitutes the refereed proceedings of the Third International Conference on Language and Automata Theory and Applications, LATA 2009, held in Tarragona, Spain, in April 2009. The 58 revised full papers presented together with 3 invited lectures and two tutorials were carefully reviewed and selected from 121 submissions. The papers address all the various issues related to automata theory and formal languages.